2019
DOI: 10.18823/asiatefl.2019.16.3.21.1042
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perceptions towards the Use of Maritime English Textbooks in Vocational School

Abstract: Ahmad Dahlan University and a Masters from Sarjanawiyata Tamansiswa University. Her research interests include curriculum design, curriculum development, instructional design, and teacher training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…They concluded that teachers held positive attitudes towards the textbooks. Other studies (e.g., Khosiyono et al., 2019 ; Okitasari and Palupi 2019 ; Khodabandeh and Mombini, 2018 ; Tawalbeh, 2018 ) came to similar conclusions. They reported that EFL teachers considered textbooks an effective source for learners.…”
Section: Literature Reviewsupporting
confidence: 57%
See 3 more Smart Citations
“…They concluded that teachers held positive attitudes towards the textbooks. Other studies (e.g., Khosiyono et al., 2019 ; Okitasari and Palupi 2019 ; Khodabandeh and Mombini, 2018 ; Tawalbeh, 2018 ) came to similar conclusions. They reported that EFL teachers considered textbooks an effective source for learners.…”
Section: Literature Reviewsupporting
confidence: 57%
“…They stated that the e-textbooks enhanced leaners' vocabulary, pronunciation and communication competence. Khosiyono et al (2019) studied EFL teachers' attitudes towards the use of Martime English textbooks. They concluded that teachers held positive attitudes towards the textbooks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study about teachers' perspective relates to the language teacher cognition research. It is also understood as the investigation of "what language teachers think, know, believe, and the relationships of these mental constructs to what teachers do in the language teaching classroom" ( Khosiyono, Pardjono, & Priyana, 2019 ). Neil England adds this work which is normally informed by broader constructs of teachers' knowledge in general, as opposed to the specialized knowledge of language teachers (England, 2017).…”
Section: Teacher and Students' Perspectivesmentioning
confidence: 99%